Efficiency of Real Estate Firms in Malaysia and its Correlates - Muhammad Ridhuan Bos Abdullah; Selamah Maamor; Mohd Zaini Abdul Karim (International Journal of Supply Chain Management, 2019)
This study estimates efficiency and examine factors that influence efficiency of Malaysian real estate firms in Malaysia. In the first stage, we estimate the efficiency level of real estate firms by employing the frontier efficiency methodology data envelopment analysis (DEA) approach. In the second stage, the Tobit Model was estimated to determine factors that influence efficiency obtained in the first stage. The data employed in this study consists of 67 real estate firms listed in the Kuala Lumpur Stock Exchange (BSKL). The results indicate that the highest average efficiency score is 0.70 which is being achieved by 23 firms or 34% of the listed firms. The Tobit regression result shows that profit, market share, and foreign share positively affects the efficiency of the real estate firm while cost negatively affect the efficiency as predicted.